ROLE PLAY TECHNIQUE TO IMPROVE PUBLIC SPEAKING ABILITY OF IIBS AR ROHMAN KALISAT JUNIOR HIGH SCHOOL STUDENTS - Arbiah, Rodiyatul; Suharmawan, Wahid; Magfiroh, Nasruliyah Hikmatul; Mujaddidi, Muhammad (Jurusan Bimbingan dan Konseling, 2025)
This study aims to determine the effectiveness of the role play technique in improving students' public speaking skills at SMP IIBS AR RAHMAN Kalisat. The research employed a quantitative approach with an experimental method. The research design used was a pre-experimental design of the one-group pretest-posttest type. The subjects were students who experienced difficulties in public speaking. Data were collected using performance-based tests conducted before and after the treatment. The results showed a significant improvement in students’ public speaking abilities after the implementation of the role play technique. The average public speaking score increased from 18 (low category) in the pretest to 32.6 (high category) in the posttest. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.018, which is less than 0.05, indicating a significant difference between the pretest and posttest results. These findings indicate that the role play technique is effective in enhancing students’ public speaking skills. The implication of this study is that teachers may consider using role play as an alternative, engaging, and interactive teaching method to develop students’ communication skills. The novelty of this study lies in the systematic application of role play techniques within the context of public speaking instruction at an integrated Islamic junior high school level. Keywords: Public Speaking, Student SMP, Role Play Technique